Profil Nyeri pada Otot Pengunyahan dan Sendi Temporomandibular pada Pasien dengan Bruxism: Artikel Orisinal - Ista Meidarlina; Rasmi Rikmasari; Sana Giovani Pramudita (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2026)
Abstract Aims: To determine the pain profile of masticatory muscles and temporomandibular joint (TMJ) in bruxers in relation to the location and the type of the pain. Materials and Methode: This research was a retrospective study using secondary data from the medical records of 30 bruxism patients treated at the Prosthodontics Clinic Dental and Oral Hospital of Universitas Padjadjaran between 2023 and 2025. Inclusion criteria included patients with a complete diagnosis of bruxism. Exclusion criteria included medical records without the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) examination. Data were analyzed using quantitative descriptive analysis to identify the location and characteristics of muscle pain. Results: Data obtained from 30 medical records that met the inclusion and exclusion criteria showed that masticatory muscle pain frequently occurred in the masseter (70%), temporalis (56,67%), pterygoid lateral (46,67%), pterygoid medial (3,33%), and other muscles (13,33%). Pain in the temporomandibular joint (TMJ) was also found (63.33%). The types of muscle pain consisted of local myalgia (63.33%), myofascial muscle pain (20%), and no pain (16,67%). Conclusion: The common site of masticatory muscle pain in bruxers was pain in the masseter muscles and also found in TMJ, with the most common type of muscle pain was local myalgia